2014
DOI: 10.4314/evj.v17i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium in Calves, Lambs and Kids at Haramaya, eastern Ethiopia

Abstract: A cross sectional study was carried out from November 2010 to April 2011 to determine the prevalence of Cryptosporidium in calves, lambs and kids and to assess potential risk factors in Haramaya, eastern Ethiopia. Hence, fecal samples from a total of 237 study animals (133 calves, 63 lambs and 41 kids) were tested with Sheather's flotation technique and Modified Ziehl-Neelsen Staining. Accordingly, the overall prevalence was found to be 23.6% (56/237) with the prevalence of 27.8% (37/133) in calves, 22.2% (14/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
7
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
9
7
3
Order By: Relevance
“…It is also possible that the hygienic conditions of animal husbandry and grazing practices may have influenced the exposure of animals to Cryptosporidium infection. The higher detection rate in male sheep and goats than in females in this study may be because males are more likely than females to disperse to other colonies or be moved to other pens especially when the females are on heat thereby promoting the dissemination of the oocysts This report is similar with the findings of other researchers (Regassa et al, 2013;Akinkuotu & Fagbemi, 2014), in sheep, and in other species by (Maikai et al, 2009). Although, Cryptosporidium infection is known to be associated with diarrhea (Caccio et al, 2013;Danladi & Ugbomoiko, 2015), in this study, small ruminants with well-formed faeces also showed a high rate of infection with Cryptosporidium oocysts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is also possible that the hygienic conditions of animal husbandry and grazing practices may have influenced the exposure of animals to Cryptosporidium infection. The higher detection rate in male sheep and goats than in females in this study may be because males are more likely than females to disperse to other colonies or be moved to other pens especially when the females are on heat thereby promoting the dissemination of the oocysts This report is similar with the findings of other researchers (Regassa et al, 2013;Akinkuotu & Fagbemi, 2014), in sheep, and in other species by (Maikai et al, 2009). Although, Cryptosporidium infection is known to be associated with diarrhea (Caccio et al, 2013;Danladi & Ugbomoiko, 2015), in this study, small ruminants with well-formed faeces also showed a high rate of infection with Cryptosporidium oocysts.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of Cryptosporidium oocysts in sheep reported here is higher than 11.7% prevalence in Kebbi State, Nigeria (Danladi & Ugbomoiko, 2015), 16% prevalence in Jos, Plateau State, Nigeria (Pam et al, 2013) and 22.2% prevalence in Ethiopia (Regassa et al, 2013), but it was lower than the 40% prevalence reported in University teaching farm in Nigeria (Akinkuotu & Fagbemi 2014). Similarly, the prealence of Cryptosporidium infection found in goats in Potiskum is higher than prevalence found 1(1.8) (6.0-8.1 × 5.0-6.5 Mean = 7.4-5.5, (OIE, 2008;OIE, 2016) in goats in Kebbi State, Nigeria (17.1%) (Danladi & Ugbomoiko, 2015) and 12.2% prevalence in Ethiopia (Regassa et al, 2013) but similar prevalence (24%) was recorded in Jos, Plateau State, Nigeria (Pam et al, 2013). The prevalence in goats was rather lower than 72.5% recorded in Veracruz, Mexico (Romero-Salas et al, 2016).…”
Section: Discussioncontrasting
confidence: 56%
“…It has been shown that the breed of small ruminants has no significant influence on the prevalence of Cryptosporidium oocysts (Regassa et al, 2013;Kaupke et al, 2017), which is consistent with the findings in this study. Nine areas were identified as the major sources of these sheep and goats in Potiskum livestock market with small ruminants from Ngalda having the highest prevalence 36.4%.…”
Section: Discussionsupporting
confidence: 92%
“…The 20% prevalence of Cryptosporidium species oocysts in sheep in this study is similar to the report of Regassa et al (2013) who recorded 22.2% in sheep in Ethiopia. However, it is higher as compared to the 11.7% reported by Danladi and Ugbomoiko, (2015) and 16.0% by Pam et al (2013) in Nigeria.…”
Section: Discussionsupporting
confidence: 90%
“…Another study conducted in Johor by Muhid et al [ 16 ] reported that the overall prevalence of Cryptosporidium infection in pre-weaned and post-weaned calves was 27.1% (65/240) indicating a higher prevalence of infection compared to the present study. The dissimilarity in the prevalence among countries may be due to a different amount of stocking rate and different management system in the farm [ 17 ].…”
mentioning
confidence: 99%